2020
DOI: 10.1111/jcal.12486
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality in language learning: A state‐of‐the‐art review of 2014–2019

Abstract: This systematic review study synthesizes research findings pertaining to the use of augmented reality (AR) in language learning. Published research from 2014 to 2019 has been explored and specific inclusion and exclusion criteria have been applied resulting in 54 relevant publications. Our findings determined: (a) devices and software employed for mastering AR; languages and contexts in which AR had been applied; theoretical perspectives adopted for guiding the use of AR; the number of participants in AR activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
102
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 69 publications
11
102
0
5
Order By: Relevance
“…Learning technologies experts offer different opinions on their assessment of the potential effects of AR on the pupils. These results reflect those of Parmaxi and Demetriou (2020) they also found that the majority of AR studies are mobile based.…”
Section: Literature Reviewsupporting
confidence: 90%
See 1 more Smart Citation
“…Learning technologies experts offer different opinions on their assessment of the potential effects of AR on the pupils. These results reflect those of Parmaxi and Demetriou (2020) they also found that the majority of AR studies are mobile based.…”
Section: Literature Reviewsupporting
confidence: 90%
“…According to these results, it can infer that future AR research with a focus on instructional design and students experience is required (Parmaxi & Demetriou, 2020). Hence, more studies are necessary to confirm whether AR applications can improve the learning effectiveness of abstract conceptual knowledge, increase pupils' motivation and creative thinking skills which are essential to their ability to solve problems in the 21st century.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Specifically, Khoshnevisan and Le [14] categorized the benefits of AR in language education into dimensions of learning outcomes and affective outcomes. Parmaxi, and Demetriou [15] analyzed research published between 2014 and 2019 systematically and identified the main benefits of AR in language learning, which included: (1) increase of motivation; (2) improvement of learning outcomes; (3) enhancement of interactions and (4) creation of opportunities for authentic language tasks. These reviews mainly focused on the benefits of AR technologies in language learning, other aspects such us the approaches of using AR in language learning have not been explored yet.…”
Section: Literature Review 21 Reviews Studies On Ar-enhanced Learning and Language Learningmentioning
confidence: 99%
“…AR has a relatively recent history of research and application in second language learning. In the relevant literature, recurring themes regarding the potential benefits of AR applications are: a) learning through real-time interaction, b) experiential learning, c) better learner engagement, d) increased motivation, e) effective memorization and better retention of the content (Khoshnevisan & Le 2019;Parmaxi & Demetriou 2020).…”
Section: Ar-based Language Learningmentioning
confidence: 99%